PENERAPAN SIMPLE ADDITIVE WEIGHT UNTUK SELEKSI PENERIMAAN KARYAWAN BARU: PENERAPAN SIMPLE ADDITIVE WEIGHT UNTUK SELEKSI PENERIMAAN KARYAWAN BARU - fery styawan; jirdansyawali; Muhammad Fadil Ardiansyah; Oktavian Aji Tyaz Aziz (CV. Multi Kreasi Media, 2022)
Acceptance of new employees or recruitment is important for companies to obtain new prospective employees in occupying a position. In some companies, the process of recruiting new employees is still not done in a professional manner. This is because there is no standardized, systematic method for assessing the eligibility of new recruits. The application of a decision support system for hiring new employees was built using the Simple Additive Weighting (SAW) method. This method was chosen because it can determine the weight value for each attribute, then proceed with a ranking process that will select the best alternative from a number of alternatives, in this case the alternative in question is the one who is entitled to be accepted as a new employee based on the specified criteria. Based on the test results, the system built can simplify and speed up the process of selecting new employees and assisting the Human Resources (HR) division manager in making decisions to determine new employees in a company.